2017
DOI: 10.1113/jp273670
|View full text |Cite
|
Sign up to set email alerts
|

The role of dentate nuclei in human oculomotor control: insights from cerebrotendinous xanthomatosis

Abstract: It is well known that the medial cerebellum controls saccadic speed and accuracy. In contrast, the role of the lateral cerebellum (cerebellar hemispheres and dentate nuclei, DN) is less well understood. Cerebrotendinous xanthomatosis (CTX) is a lipid storage disorder due to mutations in CYP27A1, typically characterized by DN damage. CTX thus provides a unique opportunity to study DN in human oculomotor control. We analysed horizontal and vertical visually guided saccades and horizontal antisaccades of 19 CTX p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
(98 reference statements)
1
10
0
Order By: Relevance
“…A retrospective study including Turkish patients < 18 years showed cataracts and diarrhea as predominant signs at disease onset. In this study, cerebellar signs were also more prevalent than pyramidal signs in pediatric cases [21]. In our cohort, all patients were diagnosed with CTX after neurological symptoms developed, and the mean age at diagnosis was 38.7 ± 9.6 years despite a mean onset age of 12.4 ± 10.6 years, which is consistent with the results of previous studies [7,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…A retrospective study including Turkish patients < 18 years showed cataracts and diarrhea as predominant signs at disease onset. In this study, cerebellar signs were also more prevalent than pyramidal signs in pediatric cases [21]. In our cohort, all patients were diagnosed with CTX after neurological symptoms developed, and the mean age at diagnosis was 38.7 ± 9.6 years despite a mean onset age of 12.4 ± 10.6 years, which is consistent with the results of previous studies [7,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, anti-saccades increased error rate and prolonged latencies have been found in patients with Cerebrotendineous Xanthomatosis ( 24 ), Friedreich ataxia ( 25 ), Spinocerebellar Ataxia type 1 ( 26 ), SCA2 ( 27 ), focal cerebellar lesions ( 28 ), and degenerative cerebellar diseases ( 29 31 ). A significant correlation between high-error rates of anti-saccades and loss of gray matter volume in the posterolateral cerebellum has also been reported in neurodegenerative cerebellar diseases ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar abnormalities, however, have recently been reported also in cerebellar patients. A few studies, indeed, have found increased directional error rate and prolonged latencies of anti-saccades in patients with hereditary cerebellar ataxia ( 24 27 ), focal cerebellar lesions ( 28 ), and acquired degenerative cerebellar diseases ( 29 31 ). Therefore, while the medial cerebellum, dorsal vermis, and fastigial nucleus [oculomotor vermis (OMV)], is traditionally considered the structure where saccade dynamic is regulated online ( 32 ), the cerebellar hemispheres and dentate nuclei (lateral cerebellum), conventionally not considered part of the oculomotor system, have been proposed to play a role in monitoring high-level saccadic behaviors, including the anti-saccades ( 24 , 32 – 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Late‐onset cerebrotendinous xanthomatosis is characterized by tendon xanthomas, psychiatric symptoms, and neurological symptoms, including pyramidal, cerebellar, and extrapyramidal signs in the second or third decade of life . Patients show abnormal pursuit, increased saccadic intrusions, multistep saccades, and antisaccade deficits . Chenodeoxycolic acid and statin therapy are an effective treatment and can prevent neurological involvement if started early …”
Section: Inborn Errors Of Metabolism Associated With Ocular Motor Dismentioning
confidence: 99%
“…21,45 Patients show abnormal pursuit, increased saccadic intrusions, multistep saccades, and antisaccade deficits. 46 Chenodeoxycolic acid and statin therapy are an effective treatment and can prevent neurological involvement if started early. 21,47,48…”
Section: Disorders Of Lipid Metabolismmentioning
confidence: 99%